The protective role of alcoholic extract of (Anethum graveolens) seeds on renal function in alloxan induced diabetic rabbits: Weam A. Shakir and Luma W. Khalil - Khalil, Luma W. (The Iraqi Journal of Veterinary Medicine, 2015)
This study was designed to investigate the effect of dill (Anethum graveolens) seeds in mitigating the complications of induced diabetes mellitus such as nephropathy of adult female rabbits. Thirty adult female rabbits were randomly assigned to 5 equal groups and treated daily for 45 days as follows: Control group (C) drenched tap water, control group intubated orally with 700 mg/kg B.W ethanolic extract of dill (T1), diabetic group drenched tap water (T2), diabetic group intubated orally700 mg/kg B.W of dill (T3) and diabetic group treated with insulin injection 3 I.U S/C (T4). Blood samples were collected by heart puncture at 0 and 45 days of experiment to assess renal efficiency: Serum creatinine, serum urea, and serum glutathione (GSH). The results indicated that diabetes mellitus without treatment group (T2) caused renal damage manifested by significant (P<0.05) increase in creatinine, urea and significant (P<0.05) decrease in serum glutathione (GSH) concentration. Oral intubation of alcoholic extract of dill seeds in diabetic treated group (T3) improved renal function through significant (P<0.05) decrease in serum urea, creatinine, and significant (P<0.05) increase in serum glutathione concentration (GSH). It was concluded that alcoholic extract of dill seeds was effective in reducing the complications of diabetes mellitus such as nephropathy.